Identification of subsurface archaeology at Mutaredh, United Arab Emirates, using ground penetrating radar - Santos-Assunção, Sonia; Ali, Moamen; Ali, Mohammed Y.; Francis, Diana; Sheehan, Peter; Omar, Waleed Awad; Iqbal, Muhammad Asim (Frontiers in Earth Science, 2024)
The United Arab Emirates holds great historical importance, as evidenced by many archaeological sites, such as the Jebel Hafit Tombs and the Hili Archeological Park in Al Ain. At the western edge of Mutaredh Oasis, a major new archaeological site was discovered in 2023 during a construction project. Several important archeological features have been documented, including an earthen mosque and boundary walls, Iron Age irrigation systems, and a circular stone tomb dating to the Bronze Age. However, the eastern edge of the Mutaredh site has remained unexplored to date. Ground Penetrating Radar (GPR) has been proven to be a successful method in mapping archaeological remains. Accordingly, a high-resolution GPR survey was carried out to identify the continuity of the unearthed archeological elements and delineate new unexplored features. A comprehensive 3D model of buried archaeological features was constructed using the acquired high-resolution GPR data in the eastern part of the Mutaredh site. Several selected anomalies have been observed, similar to the uncovered features in the western part of the Mutaredh site and structures documented in other nearby archaeological sites. The geometry and extension of these anomalies have enabled the possible identification of a further two Bronze Age circular tombs, as well as the delineation of a system of water channels (falaj), and irrigation networks with tree pits from the Iron Age. Moreover, walls probably belonging to the Late Islamic Age are identified. These findings suggest that Mutaredh has been a site of intensive human activity from the Bronze Age through to the Late Islamic period. Given the density of identified anomalies, further significant features are anticipated to lie buried in the immediate surrounding areas, promising continued insights into the area’s rich archaeological heritage. The findings of this study may guide archaeologists to specific locations and assist in selecting the most appropriate excavation techniques for the verification stage.